Rhetorical strategies of legitimation in the professional field of banking. Issue 2 (8th May 2020) - Siebert, Sabina; Martin, Graeme; Simpson, Gavin
Abstract: In this study, we analyse the rhetorical strategies of legitimation used by professionals when their conduct is exposed as wrong. Focusing on banking as a professional field and the conduct of bankers during the 2007–8 global financial crisis we ask two questions: what rhetorical strategies did senior bankers use to justify their actions and defend the legitimacy of their profession in the face of widespread public disapproval of banking practices? How did bankers use their professional field to legitimize their behaviour? To answer these questions, we analyse the justificatory rhetoric used by UK banking executives during the Treasury Select Committee hearings following the crisis. Drawing on our analysis we developed a typology of rhetorical strategies of legitimation used by the bankers, based in part on the concept of neutralization techniques. We argue that bankers, with some exceptions, drew largely on intra-field rhetoric, deeply embedded in institutionalized practices, to justify their behaviour and legitimize their profession. The lack of more convincing inter-field rhetoric only accentuated the mismatch between the moral universe of the bank executive and that of the traditional citizen, voter, and taxpayer.